Influence of silicon anisotropy on surface shape deviation of wafer by diamond wire saw. (October 2021) - Li, Zongqiang; Ge, Peiqi; Bi, Wenbo; Li, Chengyun; Wang, Chao; Meng, Jianfeng
Abstract: Single crystal silicon is an important material in the semiconductor industry. Slicing is the first process of silicon machining, and silicon is usually sliced by the diamond wire saw. Silicon is an anisotropic material. In slicing, properties of silicon at different positions contacting with the diamond grits on the diamond wire saw would be different. As a result, the cutting forces on the diamond grits in different positions would be different. The difference of cutting force would lead to the deviation of diamond wire saw in the direction of the wafer thickness and form surface shape deviation. The surface shape deviation would affect the amount of material removed in the subsequent process and the positioning accuracy of silicon crystal plane. In the condition that the diameter of the wafer is large or the wafer is ultra-thin, the influence of the surface shape deviation would be particularly serious. The (100), (110), (111), (112) and (120) crystal planes are studied in this paper. A diamond wire saw model considering the anisotropy of silicon is established and the sawing force is obtained. While the anisotropic properties of silicon are obtained by the coordinate transformation. The surface shape deviation of the wafer is then obtained based on the sawing force. Also, the shape of silicon the wafer is simulated. Based on the model established in this paper, the variation of the surface shape deviation with the feed angle of diamond wire saw is obtained. Experiments are carried out and the results are verified. According to the research results of this paper, certain feed angles of the diamond wire saw can be chosen to obtain the least surface shape deviation and reduce the influence of anisotropy of silicon.